The Study of Influence of Freeze-Thaw Cycles on Silty Sand in Seasonally Frozen Soil Regions. (7th April 2022) - Yu, Zhijie; Fang, Jianhong; Xu, Anhua; Zhou, Wenjun
Abstract : Freeze-thaw cycles can cause varying degrees of damage to expressway, in order to study the influence of freeze-thaw cycles on silty sand of expressway in Qinghai seasonal frozen soil regions, triaxial compression tests were carried out on silty sand under different initial freeze-thaw temperatures and freeze-thaw cycles. The stress-strain curve, secant modulus, cohesion, internal friction angle, dynamic shear modulus, and dynamic damping ratio of soil after freeze-thaw cycles were analyzed and studied. The experimental results show that the number of freeze-thaw cycles has different effects on the stress-strain curves at different initial freezing temperatures. With the increase of freeze-thaw cycles, the secant modulus of soil increases and changes in wave shape. The cohesion decreases and the internal friction angle decreases nonlinearly. The dynamic shear modulus and damping ratio do not change significantly. The change of freeze-thaw cycles will also affect the physical structure of the soil itself. The change of freeze-thaw cycles will also affect the physical structure of the soil itself. It will change the mosaic form of soil particles, the shape of soil particles, the size of soil particles and pores, and also make the redistribution of water in the soil.